Integration of periodic, sub‐wavelength structures in silicon‐on‐insulator photonic device design. Issue 3 (1st June 2020) - D'Mello, Yannick; Reshef, Orad; Bernal, Santiago; El‐fiky, Eslam; Wang, Yun; Jacques, Maxime; Plant, David V.
Abstract : Rapid advances in high‐resolution chip lithography have accelerated nanophotonic device development on the silicon‐on‐insulator (SOI) platform. The ability to create sub‐wavelength features in silicon has attracted research in photonic band and dispersion engineering and consequently made available a wide array of device functionalities. By drawing on recent demonstrations, the authors review how periodic, sub‐wavelength structures are used for passive wave manipulation in SOI device design. The optical response is evaluated for both orthogonal polarisations at the telecom wavelengths of 1310 and 1550 nm. The results offer a versatile toolkit for the integration of these features in conventional nanophotonic device geometries. Notable benefits include a fine control of dispersion, wavelength and polarisation selectivity, and broadband performance.